Uma análise antropológica da festa das Cabacinhas de Japaratuba/SE e em seu entorno - Lima, Gláucia Maria de Jesus (2020)
In January, in some municipalities of Sergipe, there is the party of cabacinhas, a celebration that has always been related to the party of Santos Reis. However, in contemporary times both celebrations no longer happen concomitantly. Here I will address the celebration in three municipalities, starting from Japaratuba, the research focus city, with recurrence in Siriri and Santa Rosa de Lima. The popular party, which materialized in these municipalities of the old Cotinguiba Valley, has a fundamental instrument in its performance and that gives name to the party: the cabacinhas, artifact made with wax that has water inside and whose function, at first, is to wet the playful. The aim of the game has been undergoing changes over time, a fact that, in a way, causes some discomfort in some of the population, both directly and indirectly involved in the celebration. For the development of this work I use discussions about rituals and their categories, since the parties are derived from this modality of cultural practice. We intend to enter the symbolic universe of the festival in an attempt to understand its importance for the formation of the cultural identity of those communities and for the maintenance of the so-called traditions which, in theory, are continuity of ancient customs, as well as their resignification in temporality